Extreme Wide Band MIMO Antenna System for Fifth Generation Wireless Systems - Alsaif, H. (Engineering, Technology & Applied Science Research, 2020)
A new compact 2×2 Multiple Input Multiple Output (MIMO) antenna is presented in this paper, suitable for the new wireless communications. The proposed design also covers the complete ultra-wideband for short wireless systems. The antenna system is characterized by a super wideband covering radio frequency (RF) band starting from 2.97GHz to 19.82GHz. The MIMO system contains two ship-shaped monopoles with trimmed edges. These antennas are printed on a single layer of Rogers Duroid RT5880Lz with relative permittivity εr=1.96 and loss tangent δ of 0.0009. The overall size of the MIMO system is 20mm×47mm×1.6mm. The peak-achieved gain is 8.12dB with nearly omni-directional isotropic far field patterns. The design and simulation has been performed via an industrial simulation code.